KEWAJIBAN MEDIASI SEBELUM GUGATAN GANTI RUGI PERDATA ATAS PELANGGARAN HAK CIPTA DI INDONESIA - Mayesha Andriana Yasmine (Universitas Sriwijaya, 2021)
Copyright is the exclusive right of the creator that appears automatically based on declarative principles. As one part of Intellectual Property Rights which has the widest scope of protected objects, copyright plays a major role in the development of the creative economy in Indonesia. However, there are problems with copyright regulations in Indonesia, namely Law Number 28 of 2014 concerning Copyright. The problem in question is contained in Article 95 paragraph 1, the norm in that article is not appropriate because it is